Augmented Reality Applications in Support of Electrical Utility Operations. (December 2020) - Sebok, Angelia; Mann, Rita; Andre, Terence; Gronstedt, Anders; Chik, Kerri; Cooley, Ian; Shell, Dustin; Anderson, Heather
The electric utilities industry is facing a potential crisis. As experienced workers are preparing to retire, new employees are being hired to take their place. These new workers lack the training and experience of the retiring workforce. This paper describes the potential use of Augmented Reality (AR) to address the challenges posed by this loss of expertise. The research effort investigated opportunities to use AR to improve knowledge transfer in the electric utilities industry.